Establishing initial auditory‐visual conditional discriminations and emergence of initial tacts in young children with autism spectrum disorder. Issue 4 (6th June 2019) - Fisher, Wayne W.; Retzlaff, Billie J.; Akers, Jessica S.; DeSouza, Andresa A.; Kaminski, Ami J.; Machado, Mychal A.
Abstract : Children with autism spectrum disorder (ASD) often display impaired listener skills, and few studies have evaluated procedures for establishing initial auditory‐visual conditional discrimination skills. We developed and evaluated a treatment package for training initial auditory‐visual conditional discriminations based on the extant research on training such discriminations in children with ASD with at least some preexisting skills in this area. The treatment package included (a) conditional‐only training, (b) prompting the participant to echo the sample stimulus as a differential observing response, (c) prompting correct selection responses using an identity‐match prompt, (d) using progressively delayed prompts, and (e) repeating trials until the participant emitted an independent correct response. Results indicated all participants mastered all listener targets, and the two participants for whom we tested the emergence of corresponding tacts showed mastery of most tacts without direct training. We discuss these results relative to prior research on listener skills and tacts.